A critical review of female firefighter protective clothing and equipment workplace challenges. (3rd June 2019) - McQuerry, Meredith; Kwon, Cassandra; Johnson, Heather
Abstract : Purpose: The purpose of this paper is to identify the challenging barriers faced by female firefighters, which limit workplace entrance and performance. Design/methodology/approach: Occupational barriers from both psychological and physiological viewpoints were explored based on previous literature and the reported experiences of female firefighters. Findings: A comprehensive review of literature synthesizes previous studies pertaining to gender anthropometric differences, female firefighters' experiences in the work environment and protective clothing issues. The physical capabilities of men and women in specific relation to performing firefighting activities are also examined. Issues of greatest concern are identified for personal protective clothing (PPC) and equipment, which have traditionally been designed for the male human form. This leads to a lack of protection, an increased risk of onsite injury, reduction in mobility and poorer comfort for female firefighters. Originality/value: This review provides an original overview of the critical workplace challenges faced by female firefighters. The need for female-specific PPC and equipment is specifically addressed to retain the growing number of women entering the male-dominated firefighting profession.